Prevalence of cardiovascular risk factors and cardiovascular prevention quality in primary healthcare in Russia and European countries: EURIKA Study results - S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2012)
Background. In the Russian Federation (RF), the prevalence of cardiovascular disease (CVD) and CVD mortality levels are very high. Selected aspects of cardiovascular risk factor (RF) control and preventive activity of healthcare professionals have been investigated in numerous studies; however, relatively little research has been done in the area of primary CVD prevention. The EURIKA Study (NCT00882336) is a multicentre international cross-sectional study which involved 12 countries. In the RF, 604 patients were enrolled in the study at 26 clinical centres. Material and methods. The participating patients were recruited during routine clinical visits. The study population included primary care and ambulatory patients aged over 50 years, with at least one additional RF, but without previously registered CVD events or CVD hospitalisations. Results. In the Russian sample, the proportion of patients under 65 years was 81,5% (mean age 58,3±7,3 years). The proportion of women was 68,2%. Mean levels of body mass index and waist circumference were, respectively, 29,6±5,1 kg/m2 and 96±14,0 cm. More than a half of the patients (54,5%) reported low levels of physical activity. Weekly alcohol consumption was 1,8±3,9 drinks; 25,5% of the patients were current smokers, and 15,4% were ex-smokers. Mean levels of systolic and diastolic blood pressure (BP) were 136,5±17,5 and 84,3±11 mm Hg, respectively. The prevalence of arterial hypertension (AH) was 80,5%, left ventricular hypertrophy – 14,3%, and microalbuminuria – only 0,7%. Family history of premature CVD, dyslipidemia (DLP), or diabetes mellitus was reported by 37,9%, 50,5%, and 15,7%, respectively. Among AH patients, 85,4% received antihypertensive therapy, but only 35,9% achieved target BP levels. Only 49,8% of DLP patients received lipidlowering therapy, with target levels of total cholesterol and low-density lipoprotein cholesterol achieved in 24,3%. Conclusion. Currently, the main target group for cardiovascular prevention in the Russian Federation is represented by women of early retirement age, with AH and low or moderate SCORE risk levels, who actively seek medical help. However, the highest risk of CVD events is observed in working-age men over 40 years, who rarely seek medical help and, therefore, are not covered by cardiovascular prevention measures.